Mainstreaming Distributive Justice into Resources Management in Nigeria: The Extent of the Petroleum Industry Act 2021 - Obi, Uche Val (Journal of Sustainable Development Law and Policy, 2025)
The distribution of petroleum resources has always been an issue of serious controversy in the Nigerian state under the previous petroleum regime. Thus, this paper examined the extent to which the newly enacted Petroleum Industry Act (PIA) 2021 has engrained distributive justice with respect to petroleum resources management. It concludes that the PIA has made giant strides towards this end, in view of the creation of the Host Communities Development Trust Fund, Frontier Basin Exploration Fund and improved environment protection measures. However, this study identified certain factors which will limit the full realisation of the distributive justice intendment of the Act. It is, therefore, submitted that until these issues are addressed, distributive justice would continue to remain elusive for petroleum resources management.